Ruthenium Water Oxidation Catalysts based on Pentapyridyl Ligands. Issue 22 (14th November 2017) - Gil‐Sepulcre, Marcos; Böhler, Michael; Schilling, Mauro; Bozoglian, Fernando; Bachmann, Cyril; Scherrer, Dominik; Fox, Thomas; Spingler, Bernhard; Gimbert‐Suriñach, Carolina; Alberto, Roger; Bofill, Roger; Sala, Xavier; et al.
Abstract: Ruthenium complexes containing the pentapyridyl ligand 6, 6′′‐(methoxy(pyridin‐2‐yl)methylene)di‐2, 2′‐bipyridine (L‐OMe) of general formula trans ‐[Ru II (X)(L ‐OMe‐κ‐N 5 )] n + (X=Cl, n =1, trans ‐1 + ; X=H2 O, n =2, trans ‐2 2+ ) have been isolated and characterized in solution (by NMR and UV/Vis spectroscopy) and in the solid state by XRD. Both complexes undergo a series of substitution reactions at oxidation state Ru II and Ru III when dissolved in aqueous triflic acid–trifluoroethanol solutions as monitored by UV/Vis spectroscopy, and the corresponding rate constants were determined. In particular, aqueous solutions of the Ru III ‐Cl complex trans ‐[Ru III (Cl)(L‐OMe‐κ‐N 5 )] 2+ ( trans ‐1 2+ ) generates a family of Ru aquo complexes, namely trans ‐[Ru III (H2 O)(L‐OMe‐κ‐N 5 )] 3+ ( trans ‐2 3+ ), [Ru III (H2 O)2 (L‐OMe‐κ‐N 4 )] 3+ ( trans ‐3 3+ ), and [Ru III (Cl)(H2 O)(L‐OMe‐κ‐N 4 )] 2+ ( trans ‐4 2+ ). Although complex trans ‐4 2+ is a powerful water oxidation catalyst, complex trans ‐2 3+ has only a moderate activity and trans ‐3 3+ shows no activity. A parallel study with related complexes containing the methyl‐substituted ligand 6, 6′′‐(1‐pyridin‐2‐yl)ethane‐1, 1‐diyl)di‐2, 2′‐bipyridine (L‐Me) was carried out. The behavior of all of these catalysts has been rationalized based on substitution kinetics, oxygen evolution kinetics, electrochemical properties, and density functional theory calculations. The best catalyst, trans ‐4 2+, reaches turnover frequencies of 0.71 s −1 using Ce IV as a sacrificial oxidant, with oxidative efficiencies above 95 %. Abstract : Pent‐up pyridyls : The chlorido ligand in the first coordination sphere of ruthenium and a dangling pyridine group enhance water oxidation catalysis by ruthenium pentapyridyl complexes.